Development of an Alginate-based edible coating to extend the shelf-life of minimally processed radish - PAVITHRA.M.S,; SASIKALA.S,; ATHMASELVI. K.A, (International Journal of Pharma and Bio Sciences, 2018)
The present study aimed to develop and evaluate the cut vegetables based edible coatings under room and refrigerated condition and the effect of blanching on minimally processed radishes. The radishes (Raphanussativus) were treated with 1%, 2%, 3% and 4% sodium alginate as an edible coating along with 2% calcium chloride was used to induce cross linking reaction with sodium alginate and 2% ascorbic acid as anti-browning agents are taken as coating material. Analytical determinations were performed in triplicate every-day for the storage period of 3 days at room temperatureand 5 days at refrigerated temperature. Minimally processed radishes were analysed for the following quality parameters like weight loss, total soluble solids, pH, ï¬rmness, titratable acidity, external color, vitamin C and microbial analysis. Alginate treatment at 3% with blanching delay changes in most of the physio-chemical parametersand sensory analysis under room and refrigeration condition.